The Miracle of Dialogue: Its Role in Conflict Resolution - Elwood, Douglas J. (Silliman Journal, 2022)
As the world faces the frightening prospect of extinction brought about by political controversy, racial bitterness, religious tension, economic disorder, and the whole disarray of international institutions, the almost forgotten art of dialogue becomes not only an option but a moral principle, and a necessary first step in resolving conflicts, large or small, at the interpersonal and societal level. This paper examins the subject of dialogue in relation to conflict resolution, in particular, the face-to-face dialogue that opens the way and make resolution possible and, in the end, effective, But two conditions are required for dialogue to take place- it must proceed from both sides, and the parties to the dialogue must persist relentlessly. Resolving a conflict through dialogue requires that each party recognizes and affirms the humanity of the other. More than face-to-face encounter, dialogue involves the spirit of conviction with openness in which each party is sensitive to the needs of the other, and willing to negotiate openly rather than force a solution by using power taactice, In the face of daily unfolding conflicts of varying magnitudes which threaten to annihilate the human race, the need for a real dialogical encounter in the spirit of genuine give and take cannot be overstressed.